Development of Interactive Games by Teachers at RA Al-Ikhlas Duyu in English Language Learning : Pengembangan Permainan Interaktif oleh Guru di RA Al-Ikhlas Duyu pada Pembelajaran Bahasa Inggris - Syam, Hijrah; Nurmala, Marifah; Ruslin, Ruslin; Faqih, Mutiara Nafilah; Wirana, Siti (Institut Riset dan Publikasi Indonesia, 2026)
This community service research is motivated by the low student motivation. This is limited English teaching methods at RA Al-Ikhlas Duyu, particularly due to teachers’ lack of formal background in English education. Therefore, the development of these interactive games were chosen as a solution to create more engaging and developmentally appropriate learning for young learners. This study employed a descriptive qualitative approach supported by quantitative data from pre-test and post-test result. The Participants consisted of 8 teachers and 60 early childhood students aged 5-6 years. The program was conducted from February to March 2026 through workshop, classroom mentoring, and direct teaching practice. The findings showed that interactive games such as Flashcard Matching, Sing and Move, and Role-Playing increased students’ participation, confidence and vocabulary mastery. The average students score improved from 58 in the pre-test to 81 in the post-test, indicating 39,6% increase. In addition, more than 75% of teachers were able to independently implement game-based learning activities. The study concludes that the interactive games are an effective, low-cost, and practical strategy for improving English learning in early childhood education